"Click" on PLGA‐PEG and hyaluronic acid: Gaining access to anti‐leishmanial pentamidine bioconjugates. Issue 8 (8th December 2017) - Scala, Angela; Piperno, Anna; Micale, Nicola; Mineo, Placido G.; Abbadessa, Antonio; Risoluti, Roberta; Castelli, Germano; Bruno, Federica; Vitale, Fabrizio; Cascio, Antonio; Grassi, Giovanni
Abstract: Pentamidine (Pent), an antiparasitic drug used for the treatment of visceral leishmaniasis, has been modified with terminal azide groups and conjugated to two different polymer backbones (PLGA‐PEG [PP] copolymer and hyaluronic acid [HA]) armed with alkyne end‐groups. The conjugation has been performed by Copper Catalyzed Azido Alkyne Cycloaddition (CuAAC) using CuSO4 /sodium ascorbate as metal source. The novel PP‐Pent and HA‐Pent bioconjugates are proposed, respectively, as non‐targeted and targeted drug delivery systems against Leishmania infections. Moreover, Pent has been encapsulated into PP nanoparticles by the oil‐in‐water emulsion method, with the aim to compare the biological activity of the bioconjugates with that of the classical drug‐loaded delivery system that physically entraps the therapeutic agent. Biological assays against Leishmania infantum amastigote‐infected macrophages and primary macrophages revealed that Pent, either covalently conjugated with polymers or loaded into polymeric nanoparticles, turned out to be more potent and less toxic than the free Pent. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2778–2785, 2018.